Distensibility of the anal canal in patients with systemic sclerosis: a study with the functional lumen imaging probe. (20th December 2012) - Fynne, L.; Luft, F.; Gregersen, H.; Buntzen, S.; Lundby, L.; Lundager, F.; Laurberg, S.; Krogh, K.
Abstract Aim Systemic sclerosis (SSc) is a generalized connective tissue disease that affects smooth muscle cells. Patients with SSc often have faecal incontinence caused by fibrotic degeneration of the internal anal sphincter (IAS). The functional lumen imaging probe (FLIP) is a novel method that allows the segmental biomechanical properties of the anal canal to be dynamically evaluated. The aim of the present study was to compare the segmental biomechanical properties of the anal canal in incontinent SSc patients and healthy controls. We hypothesized that the FLIP would reveal weaknesses of the IAS in the SSc patients. Method We performed FLIP distensions, endoanal ultrasonography and standard anal manometry on 14 incontinent SSc patients [11 women, median age 60 years (range 35–80)] and 15 healthy volunteers [12 women, median age 54 years (range 33–67)]. The anal canal was divided into three parts for the biomechanical analysis: upper (surrounded by the IAS and the puborectalis), middle (IAS and external anal sphincter) and lower (external sphincter only). Results The middle anal canal was the segment most resistant to distension in all of the subjects, but it was less resistant in the SSc patients than in the controls (P < 0.01). Correspondingly, the endoanal ultrasonography showed that the IAS of the SSc patients was thinner than normal (P < 0.05), and the anal resting and squeeze pressures were lower (P < 0.05). Only minor distensibility differences were found in the upper anal canal. No changes were found in the lower anal canal. Conclusion Faecal incontinence in SSc patients is associated with poor IAS function, causing increased distensibility of the middle anal canal.